2017
DOI: 10.1186/s40359-017-0208-x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of health behaviours in childhood for the development of internalizing disorders during adolescence

Abstract: BackgroundPoor mental health constitutes a considerable global public health burden with approximately half of all cases of poor mental health having their onset before the age of 14 years. The identification of modifiable risk factors early in life is therefore essential to prevention, however, there are presently very few longitudinal studies on health behaviours for mental health to inform public health decision makers and to justify preventive action. We examined the importance of diet quality, physical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…Further, it is also acknowledged that the findings are limited to only examining physician-diagnosed ID services, and did not examine externalizing disorders. This was primarily due to the scope of the study, complexity in ICD 9/10 codes, and to be consistent with previous research studies that linked CLASS with physician-diagnosed ID services using administrative health-care records (Wu et al 2017;McMartin et al 2012). As research suggests that externalizing disorders are also more apparent in children who are involved in bullying, specifically bullies (Kelly et al 2015) and bully-victims (Sigurdson et al 2015), future research should focus on examining this long-term relationship as well.…”
Section: Strengths and Limitationssupporting
confidence: 74%
See 1 more Smart Citation
“…Further, it is also acknowledged that the findings are limited to only examining physician-diagnosed ID services, and did not examine externalizing disorders. This was primarily due to the scope of the study, complexity in ICD 9/10 codes, and to be consistent with previous research studies that linked CLASS with physician-diagnosed ID services using administrative health-care records (Wu et al 2017;McMartin et al 2012). As research suggests that externalizing disorders are also more apparent in children who are involved in bullying, specifically bullies (Kelly et al 2015) and bully-victims (Sigurdson et al 2015), future research should focus on examining this long-term relationship as well.…”
Section: Strengths and Limitationssupporting
confidence: 74%
“…More detail on the methodology and procedures has been published elsewhere (Veugelers and Fitzgerald 2005;Wu et al 2017).…”
Section: Children's Lifestyle and School Performance Studymentioning
confidence: 99%
“…For that, a t-test was performed to compare all HRV indices used in this study and confirmed a significant difference for α2, in which group 1 presented a smaller α2 value (mean±standard deviation, 0.78±0.15) compared with group 2 (0.87±0. 16). No significant differences were found for the time or frequency domains.…”
Section: Analysis Comparing Two Groupsmentioning
confidence: 80%
“…Thus, addressing the rising prevalence of childhood obesity is a health priority [1], particularly considering the government aim of halving childhood obesity by 2030 [2]. Childhood obesity can have severe implications on a child's physical and mental health [3], which can continue into adulthood [1,4]. For example, prediabetes, high blood pressure [5], and depression [6].…”
Section: Introductionmentioning
confidence: 99%
“…For example, prediabetes, high blood pressure [5], and depression [6]. Adopting healthy behaviours in the early years of a child's life ensures good development and growth [4]. Recently, the importance of obesity prevention during childhood has been highlighted as an effective strategy to avoid excess weight gain in later life [1,7], particularly as obesity is di cult to reverse once established [8][9][10].…”
Section: Introductionmentioning
confidence: 99%